Case Report: Rapid Desensitization to Ocrelizumab for Multiple Sclerosis Is Effective and Safe - Aun, Marcelo Vivolo; Freua, Fernando; Marussi, Victor Hugo Rocha; Giavina-Bianchi, Pedro (Frontiers in Immunology, 2022)
Monoclonal antibodies have become a mainstay of treatment for many inflammatory diseases and malignancies. Multiple sclerosis is a chronic inflammatory, demyelinating and neurodegenerative disease of the central nervous system and a common cause of disability in young adults. Ocrelizumab is a recombinant humanized monoclonal antibody that targets CD20-positive B cells and which has been approved for treatment of multiple sclerosis. Although considered safe, more than 30% of patients treated with ocrelizumab developed infusion-related reactions, mostly considered mild. When they are severe, they can lead to a definite suspension of that drug. We present a case report of ocrelizumab desensitization in a female patient who presented an immediate hypersensitivity reaction (urticaria and angioedema) during the first ocrelizumab infusion. Despite mechanisms involved in the reaction were not elucidated, the procedure occurred uneventfully and permitted maintenance of first-line multiple sclerosis treatment. Desensitization should be considered a safe therapeutic option in patients with immediate hypersensitivity reactions to ocrelizumab.